2018
DOI: 10.1093/pch/pxx206
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the hidden curriculum on a paediatrics tertiary care clinical teaching unit

Abstract: Objective: The hidden curriculum is a set of influences that function at the level of organizational structure and culture which fall outside the formal curriculum, and are often unarticulated or unexplored. Learning associated with the hidden curriculum may have negative consequences on trainee educational development. The study goal was to examine how aspects of the hidden curriculum were enacted during ward rounds on a tertiary care general paediatrics clinical teaching unit (CTU). Methods: We conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Teamwork, too, emerges in discussions around the hidden curriculum. In a study exploring ward rounds in a pediatric clinical teaching unit, Doja et al (2018) described observing rules around the medical team. They reported the nature of the team dynamics as occurring in a hierarchy with students knowing when they could speak up and ask questions.…”
Section: Hidden Curriculum and Behavioral Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teamwork, too, emerges in discussions around the hidden curriculum. In a study exploring ward rounds in a pediatric clinical teaching unit, Doja et al (2018) described observing rules around the medical team. They reported the nature of the team dynamics as occurring in a hierarchy with students knowing when they could speak up and ask questions.…”
Section: Hidden Curriculum and Behavioral Skillsmentioning
confidence: 99%
“…Using an ethnographic approach, Doja et al (2018) conducted observations of interactions between medical students, residents, and attending staff during clinical rounds in a tertiary pediatric unit to explore how aspects of the hidden curriculum were enacted. They reported observing clear hierarchy within the team, whereby there were particular "rules" about who spoke and how each responded, and that physical positioning of the team reinforced a person's place in the hierarchy.…”
Section: How the Hidden Curriculum Operates In Clinical Settingsmentioning
confidence: 99%
“…Studies have shown that there is a steep and implicit hierarchy in medical teams (see for example Bould et al, 2015; Doja et al, 2018), and in the process of managing relations with my collaborator and hospital officers, the negotiated order of the hospital became evident. I also learned the implicit hospital “feeling rules” (Bellas, 1999), i.e.…”
Section: Managing Relations With the Hospital’s Pimentioning
confidence: 99%
“…According to Lempp and Seale (2004), some of the secreted curriculum consequences include "loss of idealism, adoption of a 'ritualized' professional identity, emotional neutralization, change of ethical integrity and acceptance of hierarchy" (p. 770). Other negative consequences of the secreted curriculum included weakening of moral reasoning among young people (Patenaude et al, 2003;Doja et al, 2018).…”
Section: Introductionmentioning
confidence: 99%